Simply vivaldi 4 cd's of musical genius - Flute, Bassoon (London : Union Square Music Ltd., 2007)
Includes performances by Alian Marion (flute), Giovanni Guglielmo (violin), Jane Archibald (tenor) and Nils Brown (tenor).
Disc 01. Concerto No 1. in E Major, Op. 8, RV 269, "La Primavera" (Spring) / Concerto No. 2 in G, Minor, Op. 8, RV 315, "L'Estate" (Summer) / Concerto No 3. in F Major, Op. 8, RV 293, "L' Autunno" (Autumn) / Concerto No. 4 in F, Minor, Op. 8, RV 297, "L'Inverno" (Winter) / Concerto in D Minor, Op. 8 No.9 RV 454 for Oboe, Strings 7 Continuo / Concerto in C major for Oboe, String 7 Continuo, RV 447. -- Disc 02. Concerto in C Major for Bassoon, Strings 7 Basso Continuo, RV 474 / Concerto in Concerto in E Minor for Basso Continuo, RV 484 / Concerto in G Minor for 3 Flute, Oboe, Violins Bassoon 7 Basso continuo, RV 107 / Concerto in A Minor for 2 Violins, Strings 7 Continuo, Op.3 No.8, RV 552. -- Disc 03. Concerto in F Major for Flute, Strings & Continuo, Op.10 No.1, "La Tempesta di Mare", RV 443 / Concerto in G Minor for Violin, Strings & Basso Continuo, Op.6 No.1, RV 324 / Concerto in D Major for Flute, Strings & Continuo, Op.10 No.3, :III Gardellino", RV 428 /Concerto in D Major for Violin, Strings & Basso continuo, Op.6 No.4, RV 216 / Concerto in A Minor for Flute, Strings & Basso Continuo, RV 440 /Concero in E-Flat Major for Violin, Strings & Basso Continuo, Op.6 No.2, RV 259 / Concerto in G Major for Flute, Strings & Continuo, Op10 No.6, RV 437 / Concerto in A Minor for Violin, Strings & Continuo, Op.3 No.6, RV 356. -- Disc 04. Gloria in D, RV 589 / Dixit Dominus, RV 595 / Stabat Mater, RV 621.
Keywords: Church music; Concertos (Orchestra).; Violin music